Alfalfa reference crop evapotranspiration in Colorado and its use for irrigation scheduling - Aljrbi, Abdulkariem Mukhtar, author; Davis, Jessica G., advisor; Andales, Allan A., advisor; Qian, Yaling, committee member; Hansen, Neil, committee member (Colorado State University. Libraries, 2015)
The goal of irrigation scheduling is efficient use of water such that water is applied to the field for optimal crop production. Previous studies have optimized irrigation scheduling using different models to manage sprinkler irrigation. This research evaluated approaches for obtaining alfalfa reference evapotranspiration (ETr) and its use in a new irrigation scheduling model for a furrow irrigation system. The objectives of this research were to: 1) Compare seasonal trends of daily ETr from the American Society of Civil Engineers Standardized Penman-Monteith (ASCE-SPM) equation and the Penman-Kimberly (PK) equation along a climatic gradient in Colorado, 2) Verify the agreement between calculated ETr from the ASCE-SPM equation and measured ETr from a lysimeter during the 2010 season for the Arkansas Valley of Colorado and correct the lysimeter ETr for alfalfa overgrowth, and 3) Test the ASCE-SPM ETr along with a locally adapted Kcr curve for corn in an irrigation scheduling spreadsheet tool for simulating the daily soil water deficit of furrow irrigated corn in northeast Colorado. The two reference ET equations were compared using R2, Root-Mean-Square Error (RMSE), Relative Error (RE), and index of agreement (d). The R2 values ranged from 0.93 to 0.99; d ranged from 0.98 to 0.99, RMSE ranged from 0.29 to 0.75 mm/d, and RE ranged from -6.35 to 1.91 %. In a comparison of the ASCE-SPM and PK equations at the Fort Collins and Rogers Mesa sites in 2011, differences were observed between the energy balance and aerodynamic terms of each equation. The energy budget calculated by the ASCE-SPM was generally 28% lower than the energy budget calculated by the PK equation at both locations for 2011. On the other hand, the aerodynamic term calculated by the ASCE-SPM equation was from 27 - 28 % higher than the aerodynamic term calculated from PK during most of 2011 at both locations. The second objective of this research compared alfalfa ET measured with a lysimeter in the center of a 4.06 ha furrow irrigated field at the Colorado State University Arkansas Valley Research Center in Rocky Ford, CO to the calculated values from the ASCE-SPM equation in periods of reference conditions in 2010. Four days were selected when alfalfa in the lysimeter was 50 - 55 cm tall, unstressed, completely covering the ground, but with its canopy extending beyond the outer walls of the lysimeter. On these dates, hourly lysimeter ETr was 0.08 to 0.11 mm/h higher than ASCE-SPM ETr. The theoretical surface area of the lysimeter was 9.181 m², while the observed effective canopy area was up to 12.461 m² due to overgrowth. Surface area corrections for the overgrowth increased the index of agreement (d) between hourly lysimeter ETr and ASCE-SPM ETr from the 0.96 - 0.98 range to the 0.99 - 1.0 range. These results showed that it is important to use the correct effective canopy area when computing ETr from a weighing lysimeter. The CIS model for calculating water deficit under a furrow irrigation system with the addition of some data from field measurements such as soil moisture content, gross irrigation, climate data, and plant height and leaf area index generated good results. The water deficit under corn was simulated at the Limited Irrigation Research Farm (LIRF) located near Greeley, Colorado during the years 2010, 2011 and 2012. Daily corn crop ET (ETc) calculated from daily ASCE-SPM ETr and a locally-derived crop coefficient curve (Kcr) were used by the CIS for daily soil water deficit calculations via water balance. This data was used to test a furrow irrigation system via the CIS model and to simulate the field irrigation by predicting the time and the amount of water for the next irrigation. The results showed good agreement between calculated and measured deficits where index of agreement (d) ranged from 0.5 to 0.99 for most years of this study, specifically when measurements of soil water content (SWC) were inserted bi-weekly or monthly. The RMSE did not exceed 2.54 mm when using SWC once per season in 2011, while bi-weekly measurements recorded d to be 0.96 in 2010, 0.99 in 2011 and 0.70 in 2012. Also, the CIS showed that irrigation water usage could be reduced by 30 to 50% through use of CIS.
Keywords: irrigation scheduling; evapotranspiration; model